U–Pb dating on calcite paleosol nodules: first absolute age constraints on the Miocene continental succession of the Paris Basin - V. Monchal; R. Rateau; K. Drost; C. Gagnaison; B. Mennecart; R. Toullec; K. Torremans; D. Chew (Geochronology)
Continental sedimentary successions are typically less complete and more poorly preserved than the marine record, leading to limited correlations between basins. Traditionally, intra-basin correlation employs radiometric dating of volcanic markers or relative dating based on the fossil record. However, volcanic markers may not always be present, and biostratigraphy relies on index fossils that are often sparse to absent in continental succession. Recent progress in carbonate U–Pb dating can improve correlations between continental successions by providing absolute age constraints on carbonate deposition and/or on syn- to post-depositional processes such as pedogenesis.